Inovasi Pengelolaan Sampah Berbasis Masyarakat: Studi Keberhasilan Implementasi Tempat Pengelolaan Sampah Terpadu di Kabupaten Sidoarjo - Budi Kariyawan; Ika Devy Pramudiana; Aris Sunarya (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
Waste management in Indonesia continues to face serious challenges, with waste generation reaching around 68 million tonnes per year, while the traditional landfill-based approach has become increasingly ineffective and unsustainable. This study aims to: (1) analyse the policy strategies of local government in implementing Integrated Waste Treatment Facilities (IWTFs) in Sidoarjo Regency; (2) identify the key success factors of the IWTF programme; (3) evaluate its impact on waste reduction and community participation; and (4) propose an effective governance model that can serve as best practice for other regions. Using a qualitative single case study approach, data were collected through in-depth interviews with local government officials, IWTF managers, and community leaders, as well as field observations at five IWTF sites and a review of relevant policy documents. Thematic analysis was applied within the framework of policy implementation and collaborative governance theories. The results show that IWTF success in Sidoarjo was driven by four main factors: strong political commitment supported by adequate budget allocation, a collaborative partnership between government, community, and private sector, community empowerment through economic incentives via waste banks, and a structured monitoring–evaluation system. The IWTF programme has reduced landfill waste by 35%, increased public waste-sorting participation from 20% to 68%, and generated IDR 2.4 billion annually from recycling activities. Overall, Sidoarjo’s IWTF initiative demonstrates that sustainable waste management can be achieved through decentralized, participatory, and collaborative governance backed by consistent policy and institutional capacity.